Hydroethanolic Extract of Lepidium apetalum Willdenow Alleviates Dextran Sulfate Sodium-Induced Colitis by Enhancing Intestinal Barrier Integrity and Inhibiting Oxidative Stress and Inflammasome Activation - Kwang-Youn Kim; Yun-Mi Kang; Ami Lee; Yeon-Ji Kim; Kyung-Ho Kim; Youn-Hwan Hwang (MDPI AG, 2024)
The prevalence of ulcerative colitis (UC) has surged in Asian nations recently. The limitations of traditional drug treatments, including biologics, have spurred interest in herbal medicines for managing UC. This study aimed to elucidate the protective mechanisms of hydroethanolic extract from Lepidium apetalum Willdenow (LWE) on intestinal integrity and inflammation in a dextran sodium sulfate (DSS)-induced colitis model of inflammatory bowel disease (IBD). Using UPLC-MS/MS analysis, eleven phytochemicals were identified in LWE, including catechin, vicenin-2, and quercetin. LWE restored transepithelial electrical resistance (TEER) and reduced paracellular permeability in IL-6-stimulated Caco-2 cells, increasing the expression of the tight junction proteins ZO-1 and occludin. LWE treatment alleviated DSS-induced colitis symptoms in mice, reducing body weight loss, disease activity index values, and spleen size, while improving colon length and reducing serum FITC-dextran levels, indicating enhanced intestinal barrier function. LWE suppressed NLRP3 inflammasome activation, reducing protein levels of pro-caspase-1, cleaved-caspase-1, ASC, and NLRP3, as well as mRNA levels of IL-1β, IL-6, and TNF-α. LWE treatment upregulated activity and mRNA levels of the antioxidant enzymes SOD1 and NQO1. Additionally, LWE modulated the Nrf2/Keap1 pathway, increasing p-Nrf2 levels and decreasing Keap1 levels. LWE also restored goblet cell numbers and reduced fibrosis in DSS-induced chronic colitis mice, increasing gene and protein expressions of ZO-1 and occludin. In summary, LWE shows promise as a therapeutic intervention for reducing tissue damage and inflammation by enhancing intestinal barrier function and inhibiting colonic oxidative stress-induced inflammasome activation.